Hierarchy and Helping Behavior in Work Teams: The Role of Legitimacy Perceptions - Gedik, Yeliz (My University, 2022)
Despite the prevalence of hierarchies in work life, much research has focused on their performance outcomes, paying little attention to how hierarchies affect cooperative behavior among the members of organizational units. In an effort to fill this gap, the current research investigates the relationship between the degree of hierarchy and members’ helping behavior in organizational work teams. Results from a field study conducted with 393 members of 60 work teams show that, at the team-level, hierarchies are negatively associated with helping behavior in organizational work teams, and that this relationship is moderated by members’ perceptions of hierarchy legitimacy. More specifically, when team members perceive the hierarchy to be less legitimate (i.e., less fair and less proper), hierarchy is even more negatively related to helping behavior. Yet, when team members perceive the hierarchy to be more legitimate, hierarchy does not have such a clear effect on members’ helping behavior. These findings offer important implications for organizations that seek to foster cooperative behavior among their employees and abolish the detriments of hierarchies in this respect.
Keywords: İşletme